A comparative study of radiation doses between phantom and patients via CT angiography of the intra-/extra-cranial, pulmonary, and abdominal/pelvic arteries - Karim, Muhammad Khalis Abdul; Sabarudin, Akmal; Muhammad, N.A.; Ng, Kwan Hoong (Springer Verlag, 2019)
This study aimed to evaluate effective dose and size-specific dose estimate (SSDE) of computed tomography angiography (CTA) examination using an anthropomorphic phantom. We included three CTA examination protocols to evaluate the intra- and extra-cranial arteries, pulmonary artery (CTPA), and abdominal vessels. Patient SSDEs were measured retrospectively to estimate patient dose, relative to the bodyweight of the patient and volume CT dose index (CTDIvol). Our findings revealed that the highest dose was absorbed by the left lobe of the thyroid gland during intra-/extra-cranial CTA and CTPA, that is, 14.11 ± 0.24 mGy and 16.20 ± 3.95 mGy, respectively. However, the highest absorbed dose in abdominal/pelvic CTA was the gonads (8.98 ± 0.30 mGy), while other radiosensitive organs in intra- and extra-cranial CTA, CTPA, and abdominal/pelvic CTA did not demonstrate significant differences between organs/structures with p value 0.88, 0.11, and 0.54, respectively. The estimated effective dose in intra-/extra-cranial CTA was lower in patients (0.80 ± 0.60 mSv) than in the phantom (0.83 mSv), but it was the opposite for CTPA, with the effective dose being higher in patients (7.54 ± 3.09 mSv) than in the phantom (6.68 mSv). Similar to the effective dose, only CTPA SSDEs were significantly higher in men than in women (19.74 ± 4.79 mGy versus 7.9 mGy). Effective dose and SSDE are clinically relevant parameters that can help estimate a more accurate patient dose based on a patient’s size. © 2019, Japanese Society of Radiological Technology and Japan Society of Medical Physics.